Tobacco use by youth: a surveillance report from the Global Youth Tobacco Survey project - Charles W. Warren; Leanne Riley; Samira Asma; Michael P. Eriksen; Lawrence Green; Curtis Blanton; Cliff Loo; Scott Batchelor; Derek Yach (The World Health Organization, 2000)
The Global Youth Tobacco Survey (GYTS) project was developed by the World Health Organization and the US Centers for Disease Control and Prevention to track tobacco use among youth in countries across the world, using a common methodology and core questionnaire. The GYTS is school based and employs a two-stage sample design to produce representative data on smoking among students aged 13-15 years. The first stage consists of a probabilistic selection of schools, and the second consists of a random selection of classes from the participating schools. All students in the selected classes are eligible for the survey. In 1999, the GYTS was conducted in 13 countries and is currently in progress in over 30 countries. This report describes data from 12 countries: Barbados, China, Costa Rica, Fiji, Jordan, Poland, the Russian Federation (Moscow), South Africa, Sri Lanka, Ukraine (Kiev), Venezuela, and Zimbabwe. The findings show that tobacco use in the surveyed age group ranged from a high of 33% to a low of 10%. While the majority of current smokers wanted to stop smoking, very few were able to attend a cessation programme. In most countries the majority of young people reported seeing advertisements for cigarettes in media outlets, but anti-tobacco advertising was rare. The majority of young people reported being taught in school about the dangers of smoking. Environmental tobacco smoke exposure was very high in all countries. These results show that the GYTS surveillance system is enhancing the capacity of countries to design, implement, and evaluate tobacco prevention and control programmes.